Deferoksamin Untuk Pencegahan hemokromatosis pada penderita thalassemia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1993)
Thalassemia major is an inherited diiorder of globin synthesis characterized by in effective erythropoiesis, shortened red blood cell survival, and severe anemia. Repeated transfusions are the basis of therapy for this disease. Although such therapy alleviates the anemia and its sequelae, it leads to massive iron deposition to the body tissue or hemochromatosis. These patients undergo progressive deterioration in pancreatic, hepatic and cardiac. function and usually succumb to life-theaterning arrhythmias or intractable heart failure. In the last decade, children with thalassemia major have been treated with an intensive transfusion regimen combined with continuous iron chelation with deferoxamine. Excretion of iron in response to intramuscular deferoxamine, however, is less than that achieved in response to continuous subcutaneous of intravenous infusions. Subcutaneous administration of deferoxamine is nearly (79%90%) as effective as the intravenous route, and appears to be the methode of choice. The recomended dose of deferoxamine was 20.60 mg/kg body weight. Vitamin C supplementation augments excretion of iron in response to deferoxamine in many patients. Treatment with deferoxamine has prove delay cardiac complication, prevent hepatic fibrosis, improve growth hormon secretion and survival time for patients with thalassemia major.